2017
DOI: 10.1556/2060.104.2017.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the thrombin generation profile in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multisystemic inflammatory autoimmune disorder. Thrombotic events occur at a higher incidence among SLE patients. The investigation of thrombin generation (TG) with calibrated automated thrombogram (CAT) test as a global hemostasis assay is applicable for the overall functional assessment of the hemostasis. The aim of this study was to characterize the hemostatic alterations observed in SLE by CAT assay. In this study, CAT parameters and basic coagulation parameters of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
10
2
Order By: Relevance
“…Two studies reported that generation of thrombin in SLE patients under platelet-free conditions was either delayed [103] or less extensive [104] than in controls, which apparently contrasts with the increased thrombotic risk of these patients. Notably, in the latter study the results were not affected by the aPL profile, thus ruling out an exclusive LA effect and supporting the idea that multiple biological factors might account for the unique SLE haemostatic phenotype [104]. By contrast, Pereira et al took into consideration the amount of PMP in platelet-free plasma and found that TG was dependent on PMP.…”
Section: Dysfunctional Coagulation Cascadementioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported that generation of thrombin in SLE patients under platelet-free conditions was either delayed [103] or less extensive [104] than in controls, which apparently contrasts with the increased thrombotic risk of these patients. Notably, in the latter study the results were not affected by the aPL profile, thus ruling out an exclusive LA effect and supporting the idea that multiple biological factors might account for the unique SLE haemostatic phenotype [104]. By contrast, Pereira et al took into consideration the amount of PMP in platelet-free plasma and found that TG was dependent on PMP.…”
Section: Dysfunctional Coagulation Cascadementioning
confidence: 99%
“…Clinical and biological evidence suggests the existence of extensive connections between haemostasis and inflammation [90]. Thus, not surprisingly, alterations in the deployment of the coagulation cascade constitute a distinctive feature of patients with inflammatory diseases such as SLE ( Figure 5) [81,[103][104][105]. Enhanced activation of TF pathway can, intuitively, be linked to increased inflammation-induced TF expression on endothelial cells, neutrophils, eosinophils and other cells [89,101] and has been consistently detected in SLE [106].…”
Section: Dysfunctional Coagulation Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant coagulation is detectable in immune mediated diseases (34, 107, 108, 119). Altered coagulation cascade and increased cardiovascular risk are common in asthmatic patients (181, 182), while patients with chronic spontaneous urticaria show aberrant thrombin generation but suffer no excess prevalence of cardiovascular disease (125, 141146).…”
Section: Pathophysiology Of Interactions Between Platelets and Neutromentioning
confidence: 99%
“…On the other hand, the coagulant mediators (FVIIa, FXa, and FIIa) in turn act on protease-activated receptors (PAR) inducing the expression of pro-inflammatory cytokines (3, 4). The relationships between the activation or dysfunction of the immune system and the coagulation system are evident in systemic autoimmune or immune-mediated diseases including lupus erythematosus (5, 6), rheumatoid arthritis (7, 8), and inflammatory bowel diseases (9, 10) which show an increased risk of thrombosis. A few studies suggested the involvement of blood coagulation also in some immune-mediated skin disorders whose aspects will be analyzed in the present review.…”
Section: Introductionmentioning
confidence: 99%